Radicalism in Islam: The Politicization of The Mahdawiyah Hadith Among The Mahdi Movement - Muqtada, Muhammad Rikza (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2019)
Mahdism, or the belief in the resurrection of the eschatological figure of the Mahdi remains important in Islam today. This belief, legitimated by the mahdawiyyah hadith, has allowed many individuals throughout Islamic histories to claim themselves to be the Mahdi, as well as to carry out a radical strand of Islamic movement in order to support their claim. Using a historical method, this paper studies the history and development of mahdism, along with their interpretationof the mahdawiyah hadith; and analyzes the connection of such interpretation with the rise of religious radicalism. The study argues, mahdism is linked to the practices of millenarianism, formerly existed in Jewish and Christian theology. The emergence of mahdism related to the political conflict during the power transition from the Umayyad to the Abbasid dynasty. Yet, the rise of the Mahdi movement found its support from the mahdawiyyah Hadith, which are interpreted in such a way as to legitimize the radical-subversive movement of the mahdi’s leaders, enabling mahdism to develop, ideologically, as a radical movement. This study concludes that mahdism is at once a religious and political movement aiming to bring back the glory of Islam. Religion becomes a legitimate and effective ideological framework of a political mission.